School Leadership During COVID-19: Implications for School Leadership Preparation Programs (Journal of School Administration Research and Development, 2022)
In one university-based school leadership preparation program, aspiring school principals were asked to intern virtually with principals during the COVID-19 school closures. During this internship experience, they interviewed principals about leading during a pandemic and wrote reflective responses explaining what they learned about leading during the pandemic. This case study examines the reflections and lessons learned of leading schools during COVID-19 from 27 aspiring principals in two cohorts of a university-based school leadership preparation program. The researchers employed an abductive qualitative analysis for each aspiring principals' reflection using both deductive and inductive coding methods. Findings revealed fourth themes: (1) the need for structure and organization, (2) attending humanistic needs, (3) struggling to respond to policy changes; and (4) finding meaning and uplifting morale. This study can be used to help inform and guide educational leadership preparation and development programs on how to redirect coursework and field-based experiences to better prepare aspiring school principals to lead during school closures.